A cultura popular nas aulas de educação física : usos e apropriações em uma escola pública na Serra-ES - Zandomínegue, Bethânia Alves Costa (2012)
The paper has as study object the uses and appropriations that the everyday life practitioners of a public school in the district of Serra/ES make of the popular culture in the context of the Physical Education classes. It mainly aims at understanding the productive consume of the manifestations descendent from the popular culture in the context shared, analyzing the learning figures valued by the practitioners in the relations established with that manifestations and identifying the challenges found to work at schools. To do so, it used the Study with the Everyday Life as heoreticalmethodological assumption, which data was produced with the different practitioners present in the context shared (teachers, students, pedagogical team, local community) and it uses data from different sources, like field diary, narratives, semi structures interviews and in focal group, iconographic images, videos, students relations and pedagogical documents. During the analysis process, data from different sources were articulated, considering the socio interactional context of its production. The productive consume of the popular culture in the context shared denotes the following uses and appropriations: relation between the local culture with the global one; valorization of the autonomy and the students’ participation in the knowledge construction; production of the “net knowledge”; sensation of belonging to the school community; and the approach of transversal themes, such as, gender and racism. In the relations the practitioners established with the manifestations from popular culture, the learning figures valued by them were manifested in three dimensions: “self-imbrication”, “objectification-denomination” and “distancingregulation”. Regarding the challenges found in order to insert the culture popular into daily the Physical Education lessons, it is highlighted: prejudice associated to religion of the students and families; the dispute of the symbolic power among teachers in the authorship of projects and in the acknowledgment of their productions; the level of differed participation of teachers in the performance of projects related to popular culture; and the precarious physical structure of the school.